Multivalent copper-based nano material as well as preparation method and application thereof

Two-dimensional Cu2Te nanosheets were prepared by the freezing-low temperature liquid phase peeling method and performed in situ electrochemical reduction to obtain polyvalent copper-based nanomaterials, which solved the problem of low activity of copper in the electrocatalytic C-N coupling process and achieved high efficiency Electrocatalytic urea production, yield and selectivity are significantly improved.

CN119287436AActive Publication Date: 2025-01-10HEFEI UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411464216.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-10
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

In the prior art, copper has low activity during electrocatalytic C-N coupling, and the Cu+ site is unstable, making it difficult to construct Cu0-Cu+ dual-active sites, affecting the selectivity and efficiency of urea synthesis.

Method used

Two-dimensional Cu2Te nanosheets were prepared by freezing-low temperature liquid phase peeling method, and in-situ electrochemical reduction was performed in H-type electrolytic cell, and the reduction current density was controlled to obtain multivalent copper-based nanomaterials for electrocatalytic C-N coupling Produce urea.

Benefits of technology

It has achieved efficient electrocatalytic co-reduction of nitrate and carbon dioxide to form urea at room temperature, with a yield of 10.21 mmol h-1gcat.-1 and a selectivity of 15.11%. The material structure is stable and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287436A_ABST
    Figure CN119287436A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of material science and electro-catalysis, in particular to a multivalent copper-based nano material and a preparation method and application thereof, and discloses a preparation method of the multivalent copper-based nano material, the operation steps are as follows: step 1, freezing-low temperature liquid phase stripping is performed on Cu2Te powder to prepare a two-dimensional Cu2Te nanosheet; and 2, the two-dimensional Cu2Te nanosheets are placed in an H-type electrolytic tank for in-situ electrochemical reduction, the precipitation rate of the Te elementary substance and TeO3 < 2-> is regulated and controlled by controlling the reduction current density, and then the copper-based nanomaterials with different valence states are obtained. The two-dimensional Cu2Te nanosheet is obtained through a freezing-low-temperature liquid phase stripping process, the precursor source is wide, no organic solvent needs to be added in the ultrasonic process, the method is simple and convenient to operate, and the method is a simple and convenient method for preparing a two-dimensional material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material science and electrocatalysis technology, and in particular to a multivalent copper-based nanomaterial and a preparation method and application thereof. Background Art

[0002] With the continuous increase in demand for fossil resources, it is imperative to develop efficient and low-energy methods to achieve a transformation in the energy structure. It is reported that electrocatalytic reduction of carbon- or nitrogen-containing resources can maintain global elemental balance and achieve green molecular transformation. Thus, the construction of CN bonds and the direct production of urea are achieved through CN coupling of multi-species co-electrolysis. Urea has always influenced the development of world industry and agriculture due to its important position in agriculture and chemical industry. Although electrocatalytic CN coupling shows great potential in sustainable urea synthesis, the interaction mechanism between catalytic sites and intermediate species is currently unclear. The presence of competitive hydrogenation of intermediates has a negative impact on the selectivity of urea synthesis, and it is urgent to explore corresponding strategies to promote CN coupling and urea synthesis.

[0003] It is worth noting that copper exhibits attractive performance in both nitrate reduction and carbon dioxide reduction reactions, and is therefore predicted to be the best low-cost metal for the co-reduction of nitrate and carbon dioxide to urea. However, the 3d orbital of Cu is fully occupied, which hinders charge transfer, and it is also difficult to form bonds with C or N atoms through the hybridization of 3d orbitals and 2p orbitals, resulting in low intrinsic activity. In addition, in the nitrate reduction reaction, Cu 0 It is easily poisoned by nitrite and inactivated, while in the carbon dioxide reduction reaction, high-valent copper species (Cu + or Cu 2+ ) is the key to CC coupling. Moreover, for the multi-intermediate urea production process, the activity of a single reaction site is usually limited. Therefore, in the synthesis of urea, it is necessary to construct a Cu 0 -Cu + The dual active sites adsorb and activate nitrate and carbon dioxide, respectively, and utilize the subsequently generated key intermediates *NH2 and *CO for CN coupling, which can effectively promote the formation yield and selectivity of urea. + The site is extremely unstable and can be easily reduced to Cu 0 Therefore, exploring a method for preparing multivalent copper-based nanomaterials with simple procedures and large-scale application to achieve high-efficiency electrosynthesis of urea has become the focus of attention. Summary of the invention

[0004] In order to solve the technical problems raised in the background technology, the present invention provides a multivalent copper-based nanomaterial and a preparation method and application thereof.

[0005] The present invention is implemented by the following technical solution: a method for preparing a multivalent copper-based nanomaterial, the operating steps are as follows:

[0006] Step 1: First, the Cu2Te powder is subjected to cryogenic liquid phase exfoliation to obtain a two-dimensional Cu2Te nanosheet;

[0007] Step 2: Place the two-dimensional Cu2Te nanosheets in an H-type electrolytic cell for in-situ electrochemical reduction, and control the reduction current density to regulate the concentration of Te and TeO3 2- The precipitation rate is increased to obtain copper-based nanomaterials with different valence states.

[0008] Preferably, the average particle size of the Cu2Te powder in step 1 is 10 microns, and the cryo-liquid phase exfoliation operation in step 1 is as follows: the Cu2Te powder is frozen in liquid nitrogen, and then the frozen sample is dispersed in a mixture of isopropanol and water, and placed in a freezer at -86°C for ultrasonic exfoliation, and centrifuged after the ultrasonication is completed.

[0009] Preferably, in step 1, the freezing time is 8 to 12 hours, and the ultrasonic time is 1 to 2 hours.

[0010] Preferably, the specific operation of step 2 is as follows: the two-dimensional Cu2Te nanosheets obtained in step 1 are dispersed in ethanol, and then evenly sprayed on carbon paper; in an H-type electrolytic cell, a platinum sheet is used as a counter electrode, Ag / AgCl is used as a reference electrode, carbon paper evenly loaded with two-dimensional Cu2Te nanosheets is used as a working electrode, and potassium nitrate and potassium hydroxide aqueous solutions are used as electrolytes, and a constant current is applied to react; after the reaction is completed, the carbon paper used as the working electrode is taken out, washed several times with deionized water, and then blown dry with nitrogen to obtain a multivalent copper-based nanomaterial on the carbon paper.

[0011] Preferably, the carbon paper has a size of 2×2 cm 2 The loading of 2D Cu2Te nanosheets is 1 mg / cm 2 .

[0012] Preferably, the concentration of the potassium nitrate aqueous solution is 0.1 to 0.5 mol / L, and the concentration of the potassium hydroxide aqueous solution is 1 to 2 mol / L.

[0013] Preferably, the applied constant current density ranges from 5 to 30 mA / cm 2 .

[0014] Preferably, the electrochemical reaction time is 0.5 to 1 h.

[0015] The present invention also proposes a multivalent copper-based nanomaterial and its application in electrocatalytic CN coupling synthesis of urea. The multivalent copper-based nanomaterial is prepared by the above method.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The present invention obtains two-dimensional Cu2Te nanosheets through a freezing-low-temperature liquid phase exfoliation process. The precursor source is wide, and no organic solvent needs to be added during the ultrasonic process. The method is simple and easy to operate. It is a simple method for preparing two-dimensional materials.

[0018] The in-situ electrochemical reduction process provided by the present invention can force Te to precipitate under the action of the reduction current, thereby obtaining copper-based nanomaterials with different valence states. The product has a stable structure, requires less equipment, has a simple process, short operation time, is environmentally friendly, and is suitable for large-scale production.

[0019] The copper-based nanomaterial prepared by the invention has novel structure, smooth surface and uniform size.

[0020] The multivalent copper-based nanomaterial prepared by the present invention is loaded on conductive carbon paper and can be directly used as a working electrode for electrocatalytic CN coupling. Under room temperature conditions, electrocatalytic nitrate and carbon dioxide can be co-reduced to generate urea. The urea synthesis yield is 10.21 mmol h-1 gcat.-1 and 15.11%. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the TEM image of the multivalent copper-based nanomaterial prepared in Example 1 under 5 mA / cm2 conditions ( Figure 1 (a) and XRD pattern ( Figure 1 (b)

[0022] Figure 2 This is the TEM image of the multivalent copper-based nanomaterial prepared under 10 mA / cm2 in Example 2 ( Figure 2 (a) and XRD pattern ( Figure 2 (b)).

[0023] Figure 3 This is the TEM image of the multivalent copper-based nanomaterial prepared in Example 3 under 15 mA / cm2 conditions ( Figure 3 (a) and XRD pattern ( Figure 3 (b)).

[0024] Figure 4 This is the TEM image of the multivalent copper-based nanomaterial prepared in Example 4 at 20 mA / cm2 ( Figure 4 (a) and XRD pattern ( Figure 4 (b)).

[0025] Figure 5 This is the TEM image of the multivalent copper-based nanomaterial prepared in Example 5 at 25 mA / cm2 ( Figure 5 (a) and XRD pattern ( Figure 5 (b)).

[0026] Figure 6 This is the TEM image of the multivalent copper-based nanomaterial prepared under 30 mA / cm2 in Example 6 ( Figure 6 (a) and XRD pattern ( Figure 6 (b)).

[0027] Figure 7 This is the UV image of the electrocatalytic CN coupling of the multivalent copper-based nanomaterial obtained in Example 5 ( Figure 7 (a) is before enzymatic hydrolysis, and (b) is after enzymatic hydrolysis).

[0028] Figure 8 The Faraday efficiency diagram and yield diagram of the electrocatalytic CN coupling of the multivalent copper-based nanomaterial obtained in Example 5;

[0029] Fig. 9 The present invention is a flow chart of the preparation method proposed by the present invention. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0031] Example 1

[0032] This embodiment prepares multivalent copper-based nanomaterials according to the following steps:

[0033] Step 1: Freeze the Cu2Te powder with an average particle size of 10 μm in liquid nitrogen for 12 h, then disperse the frozen sample in a mixture of isopropanol and water (the volume ratio of the two is 1:1), and then place it in a -86°C freezer for continuous ultrasound for 2 h. After the ultrasound is completed, centrifuge it to obtain a two-dimensional Cu2Te nanosheet.

[0034] Step 2: Disperse the two-dimensional Cu2Te nanosheets obtained in step 1 in ethanol and then evenly spray them on a 2×2 cm 2 On carbon paper, the loading is 1 mg / cm 2 ;

[0035] In an H-type electrolytic cell, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, carbon paper uniformly loaded with two-dimensional Cu2Te nanosheets was used as the working electrode, and 0.1 mol / L potassium nitrate and 1 mol / L potassium hydroxide aqueous solution was used as the electrolyte. A current of -5 mA / cm 2 The reaction was carried out at a constant current for 0.5 h. After the reaction was completed, the carbon paper used as the working electrode was taken out, washed several times with deionized water, and then dried with nitrogen gas to obtain multivalent copper-based nanomaterials on the carbon paper.

[0036] Figure 1 is the TEM image of the target product obtained in this example ( Figure 1 (a)) and XRD pattern ( Figure 1 (b)). TEM shows that the product is a nanosheet structure, and XRD diagram proves that the dual phases of Cu2Te and Cu2O are obtained after the reaction.

[0037] Example 2

[0038] This embodiment prepares multivalent copper-based nanomaterials according to the following steps:

[0039] Step 1: Freeze the Cu2Te powder with an average particle size of 10 μm in liquid nitrogen for 12 h, then disperse the frozen sample in a mixture of isopropanol and water (the volume ratio of the two is 1:1), and then place it in a -86°C freezer for continuous ultrasound for 2 h. After the ultrasound is completed, centrifuge it to obtain a two-dimensional Cu2Te nanosheet.

[0040] Step 2: Disperse the two-dimensional Cu2Te nanosheets obtained in step 1 in ethanol and then evenly spray them on a 2×2 cm 2 On carbon paper, the loading is 1 mg / cm 2 ;

[0041] In an H-type electrolytic cell, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, carbon paper uniformly loaded with two-dimensional Cu2Te nanosheets was used as the working electrode, and 0.1 mol / L potassium nitrate and 1 mol / L potassium hydroxide aqueous solution was used as the electrolyte. A current of -10 mA / cm 2 The reaction was carried out at a constant current for 0.5 h. After the reaction was completed, the carbon paper used as the working electrode was taken out, washed several times with deionized water, and then dried with nitrogen gas to obtain multivalent copper-based nanomaterials on the carbon paper.

[0042] Figure 2 is the TEM image of the target product obtained in this example ( Figure 2 (a)) and XRD pattern ( Figure 2 (b)). TEM shows that the product is a nanosheet structure, and XRD diagram proves that the dual phases of Cu2Te and Cu2O are obtained after the reaction.

[0043] Example 3

[0044] This embodiment prepares multivalent copper-based nanomaterials according to the following steps:

[0045] Step 1: Freeze the Cu2Te powder with an average particle size of 10 μm in liquid nitrogen for 12 h, then disperse the frozen sample in a mixture of isopropanol and water (the volume ratio of the two is 1:1), and then place it in a -86°C freezer for continuous ultrasound for 2 h. After the ultrasound is completed, centrifuge it to obtain a two-dimensional Cu2Te nanosheet.

[0046] Step 2: Disperse the two-dimensional Cu2Te nanosheets obtained in step 1 in ethanol and then evenly spray them on a 2×2 cm 2 On carbon paper, the loading is 1 mg / cm 2 ;

[0047] In an H-type electrolytic cell, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, carbon paper uniformly loaded with two-dimensional Cu2Te nanosheets was used as the working electrode, and 0.1 mol / L potassium nitrate and 1 mol / L potassium hydroxide aqueous solution was used as the electrolyte. A current of -15 mA / cm 2 The reaction was carried out at a constant current for 0.5 h. After the reaction was completed, the carbon paper used as the working electrode was taken out, washed several times with deionized water, and then dried with nitrogen gas to obtain multivalent copper-based nanomaterials on the carbon paper.

[0048] Figure 3 is the TEM image of the target product obtained in this example ( Figure 3 (a)) and XRD pattern ( Figure 3 (b)). TEM shows that the product is a nanosheet structure, and XRD diagram proves that the dual phases of Cu2Te and Cu2O are obtained after the reaction.

[0049] Example 4

[0050] This embodiment prepares multivalent copper-based nanomaterials according to the following steps:

[0051] Step 1: Freeze the Cu2Te powder with an average particle size of 10 μm in liquid nitrogen for 12 h, then disperse the frozen sample in a mixture of isopropanol and water (the volume ratio of the two is 1:1), and then place it in a -86°C freezer for continuous ultrasound for 2 h. After the ultrasound is completed, centrifuge it to obtain a two-dimensional Cu2Te nanosheet.

[0052] Step 2: Disperse the two-dimensional Cu2Te nanosheets obtained in step 1 in ethanol and then evenly spray them on a 2×2 cm 2 On carbon paper, the loading is 1 mg / cm 2 ;

[0053] In an H-type electrolytic cell, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, carbon paper uniformly loaded with two-dimensional Cu2Te nanosheets was used as the working electrode, and 0.1 mol / L potassium nitrate and 1 mol / L potassium hydroxide aqueous solution was used as the electrolyte. A current of -20 mA / cm 2 The reaction was carried out at a constant current for 0.5 h. After the reaction was completed, the carbon paper used as the working electrode was taken out, washed several times with deionized water, and then dried with nitrogen gas to obtain multivalent copper-based nanomaterials on the carbon paper.

[0054] Figure 4 is the TEM image of the target product obtained in this example ( Figure 4 (a)) and XRD pattern ( Figure 4 (b)). TEM shows that the product is a nanosheet structure, and XRD diagram proves that a dual phase of Cu2O and Cu is obtained after the reaction.

[0055] Example 5

[0056] This embodiment prepares multivalent copper-based nanomaterials according to the following steps:

[0057] Step 1: Freeze the Cu2Te powder with an average particle size of 10 μm in liquid nitrogen for 12 h, then disperse the frozen sample in a mixture of isopropanol and water (the volume ratio of the two is 1:1), and then place it in a -86°C freezer for continuous ultrasound for 2 h. After the ultrasound is completed, centrifuge it to obtain a two-dimensional Cu2Te nanosheet.

[0058] Step 2: Disperse the two-dimensional Cu2Te nanosheets obtained in step 1 in ethanol and then evenly spray them on a 2×2 cm 2 On carbon paper, the loading is 1 mg / cm 2 ;

[0059] In an H-type electrolytic cell, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, carbon paper uniformly loaded with two-dimensional Cu2Te nanosheets was used as the working electrode, and 0.1 mol / L potassium nitrate and 1 mol / L potassium hydroxide aqueous solution was used as the electrolyte. A current of -25 mA / cm 2 The reaction was carried out at a constant current for 0.5 h. After the reaction was completed, the carbon paper used as the working electrode was taken out, washed several times with deionized water, and then dried with nitrogen gas to obtain multivalent copper-based nanomaterials on the carbon paper.

[0060] Figure 5 is the TEM image of the target product obtained in this example ( Figure 5 (a)) and XRD pattern ( Figure 5 (b)). TEM shows that the product is a nanosheet structure, and XRD diagram proves that a dual phase of Cu2O and Cu is obtained after the reaction.

[0061] Example 6

[0062] This embodiment prepares multivalent copper-based nanomaterials according to the following steps:

[0063] Step 1: Freeze the Cu2Te powder with an average particle size of 10 μm in liquid nitrogen for 12 h, then disperse the frozen sample in a mixture of isopropanol and water (the volume ratio of the two is 1:1), and then place it in a -86°C freezer for continuous ultrasound for 2 h. After the ultrasound is completed, centrifuge it to obtain a two-dimensional Cu2Te nanosheet.

[0064] Step 2: Disperse the two-dimensional Cu2Te nanosheets obtained in step 1 in ethanol and then evenly spray them on a 2×2 cm 2 On carbon paper, the loading is 1 mg / cm 2 ;

[0065] In an H-type electrolytic cell, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, carbon paper uniformly loaded with two-dimensional Cu2Te nanosheets was used as the working electrode, and 0.1 mol / L potassium nitrate and 1 mol / L potassium hydroxide aqueous solution was used as the electrolyte. A current of -30 mA / cm 2 The reaction was carried out at a constant current for 0.5 h. After the reaction was completed, the carbon paper used as the working electrode was taken out, washed several times with deionized water, and then dried with nitrogen gas to obtain multivalent copper-based nanomaterials on the carbon paper.

[0066] Figure 6 is the TEM image of the target product obtained in this example ( Figure 6 (a)) and XRD pattern ( Figure 6 (b)). TEM shows that the product is a nanosheet structure, and XRD diagram proves that a dual phase of Cu2O and Cu is obtained after the reaction.

[0067] The multivalent copper-based nanomaterials prepared in Example 5 were subjected to electrocatalytic CN coupling synthesis of urea performance test in an H-type electrolytic cell: in an H-type electrolytic cell, a platinum sheet was used as a counter electrode, Ag / AgCl was used as a reference electrode, carbon paper uniformly loaded with multivalent copper-based nanomaterials was used as a working electrode, and a 0.1 mol / L potassium nitrate aqueous solution was used as an electrolyte. Carbon dioxide was introduced into the electrolytic cell system at a flow rate of 20 sccm, and different voltages (0, -0.1, -0.2, -0.3, -0.4 V (vs. RHE)) were applied to react for 1 h; the electrolyte after the cathode reaction was collected, and the electrolyte after the reaction was quantitatively analyzed by UV spectrophotometer. The results are as follows: Figure 7 and Figure 8As shown in the figure, it can be seen that the urea synthesis efficiency is as high as 15.11% at -0.1 V (vs. RHE), and the urea synthesis yield is as high as 10.21 mmol h at -0.3 V (vs. RHE). -1 g cat. -1 , proving that the obtained material has the ability to efficiently electrocatalyze CN coupling to synthesize urea.

[0068] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for preparing a multivalent copper-based nanomaterial, characterized in that: The steps are as follows: Step 1: First, the Cu2Te powder is subjected to cryogenic liquid phase exfoliation to obtain a two-dimensional Cu2Te nanosheet; Step 2: Place the two-dimensional Cu2Te nanosheets in an H-type electrolytic cell for in-situ electrochemical reduction, and control the reduction current density to regulate the concentration of Te and TeO3 2- The precipitation rate is increased to obtain copper-based nanomaterials with different valence states.

2. The method for preparing a multivalent copper-based nanomaterial according to claim 1, characterized in that: The average particle size of the Cu2Te powder in step 1 is 10 microns, and the cryo-liquid phase exfoliation operation in step 1 is as follows: the Cu2Te powder is frozen in liquid nitrogen, and then the frozen sample is dispersed in a mixture of isopropanol and water, and placed in a freezer at -86°C for ultrasonic exfoliation, and centrifuged after the ultrasonication is completed.

3. The method for preparing a multivalent copper-based nanomaterial according to claim 1 or 2, characterized in that: In the step 1, the freezing time is 8 to 12 hours, and the ultrasonic time is 1 to 2 hours.

4. The method for preparing a multivalent copper-based nanomaterial according to claim 1, characterized in that: The specific operation of step 2 is as follows: the two-dimensional Cu2Te nanosheets obtained in step 1 are dispersed in ethanol, and then evenly sprayed on carbon paper; in an H-type electrolytic cell, a platinum sheet is used as a counter electrode, Ag / AgCl is used as a reference electrode, carbon paper evenly loaded with two-dimensional Cu2Te nanosheets is used as a working electrode, and potassium nitrate and potassium hydroxide aqueous solutions are used as electrolytes, and a constant current is applied to react; after the reaction is completed, the carbon paper used as the working electrode is taken out, washed with deionized water several times, and then blown dry with nitrogen to obtain a multivalent copper-based nanomaterial on the carbon paper.

5. The method for preparing a multivalent copper-based nanomaterial according to claim 4, characterized in that: The carbon paper size is 2×2 cm 2 The loading of 2D Cu2Te nanosheets is 1 mg / cm 2 .

6. The method for preparing a multivalent copper-based nanomaterial according to claim 1, characterized in that: The concentration of the potassium nitrate aqueous solution is 0.1-0.5 mol / L, and the concentration of the potassium hydroxide aqueous solution is 1-2 mol / L.

7. The method for preparing a multivalent copper-based nanomaterial according to claim 1, characterized in that: The constant current density range is 5-30 mA / cm 2 .

8. The method for preparing a multivalent copper-based nanomaterial according to claim 1, characterized in that: The electrochemical reaction time is 0.5 to 1 hour.

9. A multivalent copper-based nanomaterial, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.

10. Application of a multivalent copper-based nanomaterial in electrocatalytic CN coupling synthesis of urea, characterized in that: The multivalent copper-based nanomaterial as claimed in claim 9 is used.

Citation Information

Patent Citations

  • Copper-based compound / copper nanoelectrode with interface synergistic effect and preparation and application of copper-based compound / copper nanoelectrode

    CN112899709A

  • Multivalent copper nano-material, preparation method thereof and application of multivalent copper nano-material as electrocatalyst in carbon capture technology

    CN113862715A

  • Copper nanoparticle catalyst for adjusting optimal current density of multi-carbon product prepared by electrochemical reduction of carbon dioxide and preparation method of copper nanoparticle catalyst

    CN113862721A

  • Nanowire structure copper / cuprous sulfide / copper mesh electrode material and preparation method and application thereof

    CN114381750A

  • Controllable preparation of high-performance electrocatalyst and application of high-performance electrocatalyst in preparation of urea through electrocatalytic coupling of carbon dioxide and nitrate

    CN114672847A